2014
DOI: 10.1039/c4cp02793k
|View full text |Cite
|
Sign up to set email alerts
|

Pressure effects on the radical–radical recombination reaction of photochromic bridged imidazole dimers

Abstract: We revealed the structure–entropy relationship of the photochromism of bridged imidazole dimers and that the radical–radical interaction could be controlled by applying high pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
(36 reference statements)
1
11
0
Order By: Relevance
“…Generally, the investigation of pressure effect on the rate of chemical reactions provides the important insights into the conformational changes during chemical reactions [14][15][16]. We previously demonstrated that the value of the activation free volume (ΔV ‡ ) for the thermal back reaction is an effective measure to evaluate the efficiency of the photochromic reaction in polymer matrix [17,18]. The other solution is to reduce the viscosity of a host polymer matrix [10,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the investigation of pressure effect on the rate of chemical reactions provides the important insights into the conformational changes during chemical reactions [14][15][16]. We previously demonstrated that the value of the activation free volume (ΔV ‡ ) for the thermal back reaction is an effective measure to evaluate the efficiency of the photochromic reaction in polymer matrix [17,18]. The other solution is to reduce the viscosity of a host polymer matrix [10,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The kinetic effect induced by pressure can be directly related to the activation volume of the reaction that passes through a transition state as shown in eq . Experimentally, the effect of pressure on reaction kinetics can be expressed in terms of the activation volume (Δ V ⧧ ), which is defined as the logarithmic pressure derivative of the rate constant. , Within transition state (TS) theory, the activation volume of, for example, barite nucleation (eq ), can be described as the difference in partial molar volumes between the TS ( V ⧧ ) and reactant species as indicated by eq . However, because of the complexity to measure the partial molar volume of the activated complex, experimentally the activation volume of the reaction can be determined from kinetic data using eq . where R is the gas constant, T (K) is the absolute temperature, and k (s –1 ) is the overall rate constant of barite formation at a given pressure under constant temperature. Induction time of mineral nucleation (hereafter nucleation time, t 0 ) and precipitation reaction rate are inversely proportional to each other; , therefore, eq can be modified to eq , where t 0 is the nucleation time of mineral precipitation, for example, barite.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, the effect of pressure on reaction kinetics can be expressed in terms of the activation volume (ΔV ⧧ ), which is defined as the logarithmic pressure derivative of the rate constant. 20,28…”
Section: Introductionmentioning
confidence: 99%
“…33 We previously demonstrated that the ΔS ‡ value for the thermal back-reaction becomes an effective measure to predict the pressure effects. 50 reaction rate of HHR is almost independent of pressure. On the contrary, the difference in the entropy between the initial biradical and the transition state is relatively large in HT and TT (ΔS ‡ = −27.1 and −34.5 J K −1 mol −1 in toluene, respectively).…”
Section: Resultsmentioning
confidence: 93%
“…Generally, the investigation of pressure effects on chemical reaction rates provides important insight into the conformational changes during chemical reactions. The activation volume Δ V ‡ estimated from the pressure dependence of reaction rates brings out the effective information to elucidate the structural changes because (Δ V ‡ ) is generally correlated with the difference in the partial molar volumes between the reactant and transition states. Recently, we demonstrated the pressure dependence of the thermal-back-reaction rates of the biradical species photogenerated from the bridged imidazole dimer derivatives to understand the relationship between the bridging-structure and the applied pressure . The thermal back-reaction of the biradical species photogenerated from pseudogem -bisDPI[2.2]PC ([2.2]PC-bridged imidazole dimer) is not affected by pressure because the structural change during the thermal back-reaction is small.…”
Section: Introductionmentioning
confidence: 99%